Image navigator–based, automated coronary magnetic resonance angiography for the detection of coronary artery stenosis - Gregory Wood; Reza Hajhosseiny; Alexandra Uglebjerg Pedersen; Simon Littlewood; Tina Juul Hansen; Radhouene Neji; Karl P. Kunze; Jens Wetzl; Bjarne Linde Nørgaard; Jesper Møller Jensen; Michael Maeng; Per Lav Madsen; et al. (Journal of Cardiovascular Magnetic Resonance, 2024)
ABSTRACT: Background: Coronary computed tomography angiography (CCTA) is recommended as the first-line diagnostic imaging modality in low-to-intermediate-risk individuals suspected of stable coronary artery disease (CAD). However, CCTA exposes patients to ionizing radiation and potentially nephrotoxic contrast agents. Invasive coronary angiography is the gold-standard investigation to guide coronary revascularisation strategy; however, invasive procedures incur an inherent risk to the patient. Coronary magnetic resonance angiography (CMRA) avoids these issues. Nevertheless, clinical implementation is currently limited due to extended scanning durations, inconsistent image quality, and consequent lack of diagnostic accuracy. Several technical CMRA innovations, including advanced respiratory motion correction with 100% scan efficiency (no data rejection), fast image acquisition with motion-corrected undersampled image reconstruction, and deep-learning–based automated planning, have been implemented and now await clinical validation in multi-center trials. Methods: The objective of the image navigator–based, automated CMRA prospective multi-center study is to evaluate the diagnostic accuracy of a newly developed, state-of-the-art, standardized, and automated CMRA framework compared to CCTA in 201 patients undergoing clinical investigation for CAD. The study protocol mandates the administration of oral beta-blockers to decrease heart rate to below 60 bpm and the use of sublingual nitroglycerine spray to induce vasodilation. Additionally, the study incorporates the utilization of standardized postprocessing with sliding-thin-slab multiplanar reformatting, in combination with evaluation of the source images, to optimize the visualization of coronary artery stenosis. Discussion: If proven effective, CMRA could provide a non-invasive, needle-free, yet also clinically viable, alternative to CCTA. Trial Registration: This study is registered at ClinicalTrials.gov (NCT05473117).